1998
DOI: 10.1080/00016359850136003
|View full text |Cite
|
Sign up to set email alerts
|

Betaine-containing toothpaste relieves subjective symptoms of dry mouth

Abstract: Subjects with dry mouth often experience irritation of the oral mucosa when using sodium lauryl sulfate containing products for oral hygiene. Betaine, or trimethylglycine, reduces skin-irritating effects of ingredients of cosmetics such as sodium lauryl sulfate. The aim of the present study was to compare the effects of a betaine-containing toothpaste with a regular toothpaste on the oral microbial flora, the condition of the oral mucosa, and subjective symptoms of dry mouth in subjects with chronic dry mouth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
0
25
1
2
Order By: Relevance
“…Our earlier study (18) suggested that betaine-containing SLS toothpaste could reduce subjective sensations of dry mouth. The xerostomic patients preferred the betainecontaining toothpaste to the placebo toothpaste representing ordinary commercially available SLS toothpastes (18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our earlier study (18) suggested that betaine-containing SLS toothpaste could reduce subjective sensations of dry mouth. The xerostomic patients preferred the betainecontaining toothpaste to the placebo toothpaste representing ordinary commercially available SLS toothpastes (18).…”
Section: Discussionmentioning
confidence: 98%
“…It diminishes the skin-irritating properties of various ingredients used in cosmetics; for example, detergents (17). Betaine, when added to the SLS-containing toothpaste, reduces the irritating effects of SLS and relieves subjective symptoms of dry mouth (18). Furthermore, betaine is an osmoprotectant in bacteria, plants, and animals, and it protects cell components against harsh conditions in vitro (19).…”
mentioning
confidence: 99%
“…Betaine is an amino acid derivative, obtained from sugar beet molasses during sugar production. Orally, it functions as an osmoprotectant and has been found to decrease chemical irritation and mechanical abrasions [25]. Olive oil has many properties helpful in ameliorating oral conditions commonly found in dry mouth patients including antimicrobial properties, lubrication, antiinflammatory, and anti-caries activities [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, betaine or trimethylglycine has been successfully used instead of sodium lauryl sulphate [28]. In a randomized controlled 6-week trial, 44% of patients with dry mouth reported relief of the symptom in the betaine group in comparison with 18% of patients receiving sodium lauryl sulphatecontaining toothpaste [23].…”
Section: Xerostomiamentioning
confidence: 98%